Factors that motivate the workers in companies of Metropolitan Lima - Arana Mayorca, Walter (2018)
The objective of this study was to identify the most relevant motivating factors for workers in production and service companies. The research design was exploratory and descriptive. The sample consisted of 1,214 workers from production and service companies in Metropolitan Lima. The instrument used for the evaluation was the J & F Test - Labor Motivation (Arana, 2017) which has a reliability of 0.88. The results show that the most relevant motivational factors for workers are: growth, salary, recognition, responsibility, achievement and other factors such as: work itself, the relationship with the boss and relations with colleagues. Consequently, it is concluded that, developing internal factors is the most relevant for workers when it comes to identifying their motivations in the company, even above external factors.